Guía didáctica para fortalecer la práctica del voleibol en los alumnos del 9 año del Colegio Particular Dr. Manuel A. Gonzales del cantón Pasaje año lectivo, 2012-2013. - Suárez Díaz, José Mauricio (2013)
The work presented then sewed in the development of a tutorial to strengthen the practice of volleyball students in ninth years of Private College Manuel A. González of Basic Education in the subject of Physical Culture.